Peran Bank Sampah “Bangkit Jaya” Dalam Mengatasi Permasalahan Sampah dan Meningkatkan Kesadaran Lingkungan di Purworejo - Atikah Riswandani; Desy Permata Hati; Fitria Amanah Widasari; Nur Ngazizah (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2023)
Environmental problems that are often found are waste caused by a lack of public awareness of environmental management. One solution to overcome this is the existence of a waste bank. This research uses a qualitative approach with descriptive methods, with data collection techniques in the form of observation and interviews with the manager of the waste bank “Bangkit Jaya” in Purworejo Regency. The results showed that “Bangkit Jaya” waste bank is a waste bankestablished to reduce community waste, keep the environment clean, and convert waste into useful items. The management of Bangkit Jaya waste bank is carried out with a structured work system, including waste collection and sorting, as well as collection by collectors. Bangkit Jaya waste bank has an important role in building community solidarity in keeping the environment clean and reducing waste.